P04 | CYTOCHEMICAL AND BIOLOGICAL EFFECT OF BIORESONANCE IN IRRITABLE BOWEL SYNDROME (European Journal of Histochemistry)
Technological advances in the field of instrumental therapies have allowed for progress in the creation of equipment capable of treating multiple pathologies through a bio-quantum approach1,2. The opportunity of exploiting electromagnetic physical energies opens new scenarios in relation to the possibilities of conditioning in a curative way the structure and functionality of specific tissues and systems of the human body1,3. In this context we can find the approach of Bioresonance Therapy (BT), which leverages the specificity of the electromagnetic signal of each biological tissue, that could in fact be the objective and means of calibrated stimulations aimed at inducing an inversion of pathobiological processes1,3. A pathology characterized by altered quality and function of tissues involved is Irritable Bowel Syndrome (IBS)1,4. Therefore, we made a study on 20 patients (12 women and 8 men, mean age of 51 years) to verify the ability of BT to influence IBS through a direct action of its low-intensity magnetic fields on the biological tissues of the affected organs1. To monitor the health of patients, we observed the values recorded, before and after the execution of a cycle of 8 BT sessions, for the Short-Form Health Survey 36, the Bristol Stool Form Scale and, above all, the Fecal Calprotectin. The results of our study suggest that BT is associated with a significant improvement in all the parameters observed and to an inversely proportional correlation between the Calprotectin values and the quality of life experienced by the patients in relation to the perceived IBS symptomatology1. Therefore, it is possible to highlight both the efficacy of the proposed treatment and the important role of the collaboration between clinical medicine and the physical and histochemical sciences in defining the validity and the possibilities of improvement attributable to innovative therapeutic techniques such as BT.